2008
DOI: 10.1210/en.2007-1710
|View full text |Cite
|
Sign up to set email alerts
|

A Conditional Knockout Mouse Line of the Oxytocin Receptor

Abstract: Oxytocin plays important roles in reproductive physiology and various behaviors, including maternal behavior and social memory. Its receptor (Oxtr) is present in peripheral tissues and brain, so a conditional knockout (KO, -/-) would be useful to allow elimination of the receptor in specific sites at defined times. We created a line of mice in which loxP sites flank Oxtr coding sequence (floxed) enable Cre recombinase-mediated inactivation of the receptor. We expressed Cre recombinase in these mice either in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
265
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(274 citation statements)
references
References 40 publications
9
265
0
Order By: Relevance
“…OT receptor (OTR) KO mice showed impaired social recognition (Takanayagi et al, 2005), in line with the findings obtained in OT KO mice. Moreover, mice from which the OT receptor was inactivated from postnatal days 21 to 28 onward also showed impaired social recognition (Lee et al, 2008). Importantly, in this study, loss of OTR binding was most prominent in the lateral septum, the hippocampus and ventral pallidum and significantly reduced in the OB and neocortex; however, it remained unchanged in the MeA.…”
Section: Oxytocin and Social Recognitionmentioning
confidence: 49%
“…OT receptor (OTR) KO mice showed impaired social recognition (Takanayagi et al, 2005), in line with the findings obtained in OT KO mice. Moreover, mice from which the OT receptor was inactivated from postnatal days 21 to 28 onward also showed impaired social recognition (Lee et al, 2008). Importantly, in this study, loss of OTR binding was most prominent in the lateral septum, the hippocampus and ventral pallidum and significantly reduced in the OB and neocortex; however, it remained unchanged in the MeA.…”
Section: Oxytocin and Social Recognitionmentioning
confidence: 49%
“…23) Similarly, Oxtr Ϫ/Ϫ mice are viable and have no obvious defects in reproductive behavior, although dams exhibit normal parturition followed by defects in lactation and maternal nurturing. 24,25) These results indicate that the OXT/OXTR/CD38 signalling pathway is not essential for normal parturition in mice, but OXT/OXTR for milk ejection, and that CD38 is not directly involved in reproduction (Table 1).…”
Section: Autistic Phenotypes In Cd38 Null Mutant Mice Both Cd38mentioning
confidence: 97%
“…3,[4][5][6][7][8][14][15][16][17][18][19][20][21] In addition, some studies have shown that increased levels of OXT in the early postnatal period may affect behavior and last into adulthood, 8,15,22) and that subcutaneous administration of low doses of OXT facilitates social recognition. 21) Two types of mice with OXT (Oxt) or OXT receptor (Oxtr) gene knockout (Oxt Ϫ/Ϫ or Oxtr Ϫ/Ϫ ) have shown profound social amnesia 14,18,[22][23][24][25][26] : Social amnesia can be fully rescued by injection of OXT into the medial amygdale in Oxt Ϫ/Ϫ mice; Impairment of social behavior is clearly observed in pups. These observations suggest that OXT plays important roles in social behavior by OXTR stimulation during brain development throughout the juvenile to adult stages.…”
mentioning
confidence: 99%
“…While OTR +/+ mice spend a longer time exploring a cage occupied by an unfamiliar mouse than an empty cage, OTR -/-mice spend the same time in exploring both cages [11]. Interestingly, forebrainrestricted OTR -/-male mice show a decline in the investigation time with the same female mice during repeated pairings and show full recovery following the introduction of a new female as with OTR +/+ male mice [12].…”
Section: Introductionmentioning
confidence: 97%